THE PREFERENTIAL STRUCTURE OF Co2+ SOLVATION IN AQUEOUS AMMONIA SOLUTION DETERMINING BY MONTE CARLO SIMULATION - Cahyorini Kusumawardani; Sukisman Purtadi; Crys Fajar Partana; Harno Dwi Pranowo; Mudasir Mudasir (Indonesian Journal of Chemistry, 2007)
A Monte Carlo simulation was performed for Co2+ in 18.6 % aqueous ammonia solution at a temperature of 293.16 K, using ab initio pair potentials and three-body potentials for Co-H2O-H2O, Co-NH3-NH3 and Co-H2O-NH3 interactions. The first solvation shell consists average of 2.9 water and 3.2 ammonia molecules, and the second shell of 10.4 water and 11.2 ammonia molecules. The structure of the solvated ion is discussed in terms of radial distribution functions, angular distributions and coordination number.